Auditory brain stem of the ferret: some effects of rearing with a unilateral ear plug on the cochlea, cochlear nucleus, and projections to the inferior colliculus - Moore, DR (J Neurosci, 1989)
To examine the influence of acoustic experience on the development of the mammalian auditory brain stem, darkly pigmented ferrets were reared with a plug inserted in the right outer ear. The plugs were first inserted on postnatal day 23–34 and produced a variable, frequency- dependent attenuation of up to 60 dB. Between 3–15 months after the ear plug was begun, animals were prepared for physiological recording and injection of wheat germ agglutinin-HRP (WGA-HRP) in the left inferior colliculus (IC). The plug was removed and the condition of the right ear was assessed by pure-tone stimulation and recordings from neurons in the left IC. Neural audiograms for each animal showed a residual deficit in most cases. Following 24–60 hr survival, the animals were perfused and the right ear was examined. Brain-stem sections were reacted with tetramethylbenzidine. Outer and/or middle ear pathology was present in over half of the animals. However, the cochleas appeared to be normal and the spiral ganglion cells were normal by several quantitative criteria: number, area, and nucleolar eccentricity. The volume of each division of the cochlear nuclei (CN) and the areas of individual neurons in the anteroventral CN were the same on the right and left sides. The number of CN neurons retrogradely labeled from the left IC injection of WGA-HRP was found to be significantly increased in the left CN, relative to normal animals, when expressed as a ratio of the number labeled in the right CN. We conclude that the residual hearing loss in the previously plugged ears was predominantly or exclusively conductive. Neonatal, unilateral conductive hearing loss in the ferret does not lead to degeneration of the CN on the side of the loss, but it does lead to at least one rearrangement of auditory brain- stem connectivity. We suggest that the extent to which the brain stem is modified by early auditory deprivation is dependent on the type, degree, and symmetry of the hearing loss.